Corporate Governance as a Determiner of Tax Avoidance: A Literature Review Study - Lubis, Citra Windy; Kesuma, Sambas Ade; Muda, Iskandar (Ridwan Institute, 2023)
Tax avoidance is an act of legally reducing taxes or taking advantage of loopholes in tax laws. Some aspects of corporate governance that are often used in tax avoidance research are ETR, Incentives, company board composition, company ownership structure, Auditor Quality, and customers. This study uses a literature review research method using 34 articles related to tax avoidance and corporate governance starting from 2006 – 2022. More research on tax avoidance was carried out in 2018 with the aspect of governance that is most often researched is the structure of corporate ownership which is more many use agency theory as a basis for research. A low ETR reflects a low tax burden resulting from tax evasion. Empirical evidence suggests that an independent and strong board composition will have a negative impact on tax evasion. The company's ownership structure has an impact on the separation of ownership and control which can encourage tax evasion. The auditor's reputation is the most important thing that must be maintained by an auditor so that it is likely that the auditor is less tolerant of companies trying to avoid taxes committed by their clients. Customers can be used as a tax strategy that companies can use to avoid taxes